Proposing a Balance Competency and Cultural Fit Recruitment Strategy in Startup Company (Case: Beta) - Farasila, Iraisa; Putra Pratama, Andika (DINASTI RESEARCH, 2025)
This study aims to develop a recruitment strategy that balances the assessment of competencies and cultural fit at BETA, an ed-tech startup in Indonesia. The research focuses on recruitment challenges, including lengthy hiring processes and high probationary failure rates due to mismatches in competencies and cultural alignment. A qualitative approach was employed, involving in-depth interviews with six key informants from BETA’s Talent Acquisition team and division leaders. Data analysis was conducted using the Interactive Model Analysis, which includes data collection, condensation, display, and conclusion drawing. The findings reveal that key competencies required include a strong work ethic, a lifelong learning mindset, and innovation, while cultural values prioritized collaboration, commitment to learning, and optimism. The proposed recruitment strategy involves detailed job specifications, competency-based interview guidelines, cultural fit assessments, structured probationary workflows, and clear Key Performance Indicators (KPIs) for objective evaluation. Implementing these strategies is expected to enhance recruitment efficiency, reduce probationary failures, and build a team that is both competent and culturally aligned.